Children’s literature and the politics of gender* - Jarkovská, Lucie (Wydawnictwo Naukowe UAM, 2014)
The article discusses children’s literature as a matter that can become highly politicized. While often viewed as apolitical, stories for children have always been subjected to hegemonic ideologies and mediated dominant norms. The analysis focuses on gender dimension of this normativity and shows that the attempts to create gender subversive stories for children have to face not only the conservative backlash but they also have to deal with wider cultural context and contemporary meanings of childhood. The last section of the article shows that no matter how gender balanced or stereotypical a story is, the interpretation lies with children themselves. Thus, researchers analyzing messages in children’s stories always have to take into account young readers and their diverse ways of understanding.
Keywords: children’s literature; gender; gender subversion; innocence; sexuality